FILL REMOVAL FROM HORIZONTAL WELLBORE USING FOAM IN COILED TUBING - KHAN, JAVED AKBAR (2013)
Coiled tubing is extensively used in oil industry to clean the wellbore to increase the productivity of oil/gas well by removing the fill/sand downhole. Well cleanup operation for large diameter well with low bottomhole pressure is problematic and common cleanout fluids are not effective as a circulation fluid due to severe pressure losses and low suspension capability. In order to mitigate such effect, foam is used as a circulation fluid because it has the highest suspension power. Foam is formed by mixing water, air and additive. Due to complexity of foam rheology, it is challenging to accurately predict foam-solids flow behaviour during coiled tubing cleanout operation.